Effect on Mechanical Properties by Layering Pattern of Natural Fibers - Kashinath H. Munde, DattatrayP. Kamble, Ashish R. Pawar, Ganesh E. Kondhalkar (Mathematical Statistician and Engineering Applications, 2020)
Banana fibers and Kenaf fibers are natural fibers with good tensile strength. We can prepare epoxy based biocomposite from these fibers. In this work, banana (B) and kenaf (K) fibers reinforced unidirectional (UD) hybrid biocomposites are prepared. Totally two plates are manufactured. First Plate is 4 layer unidirectional 15% Banana + 15% Kenaf fibers alternate layers composite (UD B-K-B-K). Second Plate is 4 layer 15% Banana + 15% Kenaf fibers cumulative layers composite (UD B-B-K-K). Tensile, Flexural and Izod impact tests are carried out as per ASTM standards. Effect of layering sequence on these mechanical properties is investigated experimentally. It is found that cumulative layer (UD B-B-K-K) has better tensile and flexural strength than alternate layers (UD B-K-B-K) biocomposite. Whereas alternate layer (UD B-K-B-K) biocomposite shows better impact strength than cumulative layer (UD B-B-K-K) biocomposite.